Steady 3D incompressible flow analysis for the simplified train-tunnel interaction - Kim, Sungcho; Soni, Bharat K. (Computer Assisted Methods in Engineering and Science, 2023)
This paper describes the phenomena that occur when a simplified model of train interacts with the tunnel at three locations - before, entering and leaving the tunnel. The Navier- Stokes equation is solved by introducing the artificial compressibility to change the governing equation type from the elliptic to hyperbolic. The Baldwin- Lomax turbulence modeling is employed to simulate the flow field with a Reynolds number of 106, and the computation domain is divided into three blocks considering the train and tunnel geometries. The grid is algebraically adapted determining the maximum solution change plane and solution weighting factors. The pressure in the adapted solution is not changed much, however, the skin friction is severely varied comparing with those of the non-adapted solutions. When the train enters into the tunnel, there are large increase in the surface pressure and skin friction distribution on the train surface.